An Analysis Regarding the Ultimate Outcome of Abstracts Presented at the European Paediatric Surgeons' Association Congress - Gerçel, Gonca; Durakbaşa, Çiğdem Ulukaya (European Journal of Pediatric Surgery, 2024)
Introduction The objective of this study is to analyze the conversion rate of abstracts presented at the European Paediatric Surgeons' Association (EUPSA) congress into full-text publications and to conduct a thorough analysis of the attributes and quality of the papers published.Materials and Methods Abstract books including the years 2017 to 2022 were reviewed. Searches on PubMed and Google Scholar, utilizing keywords from the titles and the author names, were conducted to trace subsequent full-text publications. A categorical analysis detected variations and trends, with a significance threshold of p < 0.05. Quantitative data were presented as means ± standard deviations, whereas categorical data were represented as counts (n) and percentages (%).Results A total of 2,139 abstracts were presented at the EUPSA annual meetings during five consecutive congresses. The average number of presented abstracts was 427.6 ± 20.4 per year from across 63 different countries. European countries contributed the majority (71%). The presentations included both oral (n = 817, 38.2%) and poster presentations (n = 1,322, 61.8%). They predominantly focused on clinical topics (90.6%). Single-center retrospective studies were the most common study design (43.7%). Out of all abstracts presented, 1,033 (48.3%) were published within an average time interval of 1.39 ± 1.19 years after presentation. Most journals had an impact factor (IF) between 1 and 5 (74.5%). There was no significant year-to-year variation in publication rates (p = 1). Basic science studies were published in journals with significantly higher IF compared with clinical studies (p < 0.001).Conclusions The publication rate of abstracts presented at the EUPSA annual congress stands at 48.3%, aligning with the rates observed in other similar studies. This suggests that abstracts submitted to the EUPSA congresses were evaluated and scored rigorously, adhering to international selection criteria. Furthermore, the majority of these abstracts were published in journals with moderate to high IFs, providing quantitative evidence of the scientific quality of research within the field of pediatric surgery.
Keywords: EUPSA; journals; meeting abstracts; publication rate; pediatric surgery